An Analysis on Schmidt V.A.’s Discursive Institutionalism and its implications to Taiwan’s Teacher Professional Development Policy - Lin, Shu Chi (Technium Social Sciences Journal, 2020)
This Thesis explored the theory, practices, and future prospects of the teacher professional development policy in Taiwan. Prof. Schmidt’s discursive institutionalism pointed out an analysis of institutions must start from the ideas and discourses of the actors and must regard the coordinative political sphere of the policy for a policy idea to be communicated and become the consensus of political elites. Additionally, the top-down communicative political sphere was essential for ideas to be imparted to the general public. The length of participation in the professional policy in Taiwan was, on average, one to two years, because teachers there considered the policy unrelated to their classroom teaching. Although teachers were aware of the need to grow, few, in fact, take actions while most remained passive and stayed inertia. This thesis argued that the languages of a policy idea were transmitted both by a top-down and bottom-up approach. If a ruling government fails to construct an effective discourse, its policy will not be successfully implemented.